(Table 1) Summary of densities and compressional-wave velocities at DSDP Hole 72-516F - Gebhard, S N; Carlson, Richard L (Supplement to: Gebhard, SN; Carlson, RL (1983): Compressional-wave velocities in basalts from the Rio Grande Rise. In: Barker, PF; Carlson, RL; Johnson, DA; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 72, 577-579, https://doi.org/10.2973/dsdp.proc.72.125.1983, 1983)
Compressional-wave velocities were measured in 9 samples from the 18 m of igneous basement penetrated by drilling at Hole 516F. Wet-bulk densities range from 2.50 to 2.92 g/cm**3; compressional-wave velocities (measured at 0.4 kbar confining pressure) range from 4.29 to 6.32 km/s. Because of progressive alteration, compressional-wave velocities in deep-sea basalts tend to decrease with age; velocities in basalts from immediately beneath the sediment/basement contact are consistent with the proposed age (86 ± 4 Ma) of basement at the site. A very strong vertical velocity gradient of 0.126 km/s/m in the 18-m basement interval reflects a marked decrease in the degree of alteration with depth beneath the contact.